Structural and functional basis of the selectivity filter as a gate in human TRPM2 channel - Xiafei Yu (Elsevier, 2021)
Summary: Transient receptor potential melastatin 2 (TRPM2), a Ca2+-permeable cation channel, is gated by intracellular adenosine diphosphate ribose (ADPR), Ca2+, warm temperature, and oxidative stress. It is critically involved in physiological and pathological processes ranging from inflammation to stroke to neurodegeneration. At present, the channel’s gating and ion permeation mechanisms, such as the location and identity of the selectivity filter, remain ambiguous. Here, we report the cryo-electron microscopy (cryo-EM) structure of human TRPM2 in nanodisc in the ligand-free state. Cryo-EM map-guided computational modeling and patch-clamp recording further identify a quadruple-residue motif as the ion selectivity filter, which adopts a restrictive conformation in the closed state and acts as a gate, profoundly contrasting with its widely open conformation in the Nematostella vectensis TRPM2. Our study reveals the gating of human TRPM2 by the filter and demonstrates the feasibility of using cryo-EM in conjunction with computational modeling and functional studies to garner structural information for intrinsically dynamic but functionally important domains.